[De La Salle Naval ROTC unit won first place in the inter-unit tournament in gunnery, seamanship and signaling] - Naval ROTC - De La Salle University, Manila (Animo Repository, 1953)
The De La Salle Naval ROTC unit won first place in the annual inter-unit tournament in gunnery, seamanship and signaling in which all Naval cadets participated. The cadet officers staff of this unit was also appointed the Corps Command of the composite battalion of naval cadets from all institutions.